Nerve Reconstruction’s Revolutionary Effect on Facial Paralysis: An Editorial - Boueri, Myriam; Nicolas, Gregory; Fernandes, Thadeu (International Journal of Clinical Research, 2024)
Introduction: Facial paralysis can impact a person’s capacity to communicate and interact with others, as well as their physical appearance. [1] A ray of hope has been offered by the development of microsurgical methods for treating this debilitating illness. A game-changing procedure among these is nerve reconstruction using muscle grafts or merely nerves, such as the muscle gracilis. In this editorial, we explore the value of nerve repair in cases of facial paralysis and highlight the encouraging effects of microsurgical procedures.